Structural peculiarities of vegetative organs of Sempervivum tectorum L. (Crassulaceae) and Saliсornia europaea l. (Chenopodiaceae) - residents of extreme habitats = структурні особливості вегетативних органів Sempervivum tectorum L. (Crassulaceae) та Saliсornia europaea L. (Chenopodiaceae) - мешканців екстремальних місцезростань = структурные особенности вегетативных органов Sempervivum tectorum L. (Crassulaceae) и Saliсornia europaea L. (Chenopodiaceae) - жителей экстремальных местообитаний - N. A. Kirilenko (Kazimierz Wielki University, 2016)
Kirilenko N. A. Structural peculiarities of vegetative organs of Sempervivum tectorum L. (Crassulaceae) and Saliсornia europaea l. (Chenopodiaceae) - residents of extreme habitats = структурні особливості вегетативних органів Sempervivum tectorum L. (Crassulaceae) та Saliсornia europaea L. (Chenopodiaceae) - мешканців екстремальних місцезростань = структурные особенности вегетативных органов Sempervivum tectorum L. (Crassulaceae) и Saliсornia europaea L. (Chenopodiaceae) - жителей экстремальных местообитаний Journal of Education, Health and Sport. 2016;6(9):883-892. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162170 http://ojs.ukw.edu.pl/index.php/johs/article/view/3945   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. UDK: 582.715:581.48+581.8 STRUCTURAL PECULIARITIES OF VEGETATIVE ORGANS OF SEMPERVIVUM TECTORUM L. (CRASSULACEAE) AND SALIСORNIA EUROPAEA L. (CHENOPODIACEAE) - RESIDENTS OF EXTREME HABITATS N. A. Kirilenko Odessa I. I. Mechnykov National University Anatomical-morphological characteristics of leaves and stems of plants of succulent type Sempervivum tectorum L. and Salicornia europaea L. from extreme habitats were studied. Basic quantitative parameters of anatomical indices were presented. The comparative analysis of the structure of vegetative organs of succulents was carried out. A number of common features, which result from adaptation to such conditions of growth (characteristic peculiarities of the external structure, weak differentiation of mesophyll, considerable development of the water-bearing tissue CAM - type of photosynthesis) and features, which distinguish the studied species (the type of leaf mesophyll, presence of trichomes, type of the stomata apparatus, the degree of the conductive system development) were registered. Key words: anatomy, stem, leaf, plants of succulent type, extreme habitats.   СТРУКТУРНІ ОСОБЛИВОСТІ ВЕГЕТАТИВНИХ ОРГАНІВ SEMPERVIVUM TECTORUM L. (CRASSULACEAE) ТА SALIСORNIA EUROPAEA L. (CHENOPODIACEAE) - МЕШКАНЦІВ ЕКСТРЕМАЛЬНИХ МІСЦЕЗРОСТАНЬ Н. А. Кириленко Одеський національний університет імені І. І. Мечникова Вивчено анатомо - морфологічні характеристики листків та стебел рослин сукулентного типу Sempervivum tectorum L. та Salicornia europaea L. з екстремальних місцезростань. Представлено основні кількісні параметри анатомічних показників. Проведено порівняльний аналіз будови вегетативних органів сукулентів. Відмічено низку спільних ознак, які є результатом пристосування до подібних умов зростання (характерні особливості зовнішньої будови, слабка диференціація мезофілу, значний розвиток водоносної тканини, САМ - тип фотосинтезу) та ознаки, які відрізняють досліджувані види (тип мезофілу листка, наявність трихом, тип продихового апарату, ступінь розвитку провідної системи). Виявлено взаємозв'язок анатомічної будови з функціональною активністю рослин та умовами середовища існування. Ключові слова: анатомія, стебло, листок, рослини сукулентного типу, екстремальні місцезростання. СТРУКТУРНЫЕ ОСОБЕННОСТИ ВЕГЕТАТИВНЫХ ОРГАНОВ SEMPERVIVUM TECTORUM L. (CRASSULACEAE) И SALIСORNIA EUROPAEA L. (CHENOPODIACEAE) - ЖИТЕЛЕЙ ЭКСТРЕМАЛЬНЫХ МЕСТООБИТАНИЙ Н. А. Кириленко Одесский национальный университет имени И. И. Мечникова Изучены анатомо - морфологические характеристики листьев и стеблей растений суккулентного типа, произрастающих в экстремальных условиях. Указаны основные количественные параметры исследованных показателей. Проведен сравнительный анализ строения вегетативных органов исследуемых видов и выявлена взаимосвязь анатомического строения с функциональной активностью растений и условиями среды обитания. Ключевые слова: анатомия, стебель, лист, растения сукулентного типа, экстремальные местообитания.